Cardiac complications in a metamizole-induced type I Kounis syndrome - Jose F. Martínez Juste; Tomas Ruiz Garces; Rafael Gonzalez Enguita; Pedro Cia Blasco; Jara Altemir Trallero (Brazilian Journal of Anesthesiology, 2016)
Kounis syndrome is defined as the coincidental occurrence of allergic reaction and acute coronary syndrome secondary to vasospasm. Anti-inflammatory drugs are included as one of the multiple causes. Current data available about this syndrome come from case reports. We present the case of a patient who suffered Kounis syndrome with cardiogenic shock and asystole after intravenous infusion of Metamizole, and in which no lesions were observed in coronariography. Resumo: A síndrome de Kounis é definida como a ocorrência concomitante de reação alérgica e síndrome coronariana aguda secundária ao vasoespasmo. Os medicamentos anti-inflamatórios estão incluídos como uma das múltiplas causas. Os dados atuais disponíveis sobre essa síndrome são provenientes de relatos de casos. Apresentamos o caso de um paciente que apresentou síndrome de Kounis com choque cardiogênico e assistolia após infusão intravenosa de metamizol, e no qual não foram observadas lesões na coronariografia. Keywords: Kounis syndrome, Metamizole, Cardiogenic shock, Asystole, Palavras-chave: Síndrome de Kounis, Metamizol, Choque cardiogênico, Assistolia